Decreasing Employee Turnover though Improving Employee Engagement in PT.Central Santosa Finance - Yuniarti, Melina; Gustomo, Aurik (The Indonesian Journal of Business Administration, 2016)
Abstract. This research aim to decrease employee turnover in PT. Central Santosa Finance especially in Cimahi branch  through  finding any factor that influenced the level of Employee Engagement and maked  some improvement.Explanatory study was conducted with used employee engagement model such as: Gallup, DDI, ASTD and Aon-Hewitt as a reference and will be confirm with empirical study to find an apropriate model for PT. Central Santosa Finance. Based on that model, conducted employee engagement survey by spreading 149 questionnaire for the whole of employees in PT. Central Santosa Finance. To find the root cause of the problem IPA Matrix (Important Performance Analysis) and indepth analysis were used in this research. The result from the analysis was found there are two factors and three variable factors which should be improve; the first factor is Goal (vision and mission of company), the second is Working Condition which is have two variable; Material and equipment to do the right work and the other variable is salary, benefits, safety and work environment. This study has some recommendation to improve. There are: Socialization about the importance of company’s vision and Mission,  Building The Infrasturcture and framework, Creating Good Working Condition for Employees, Design improvements to Work Process and Working Condition and Redesign the scheme of Compensation and the last improvement is Evaluation and Controlling. Keywords: Employee Engagement, Turnover, Important Performance Analysis, Goal and Working Condition